With gratitude from RHiME: Reviewers 2019 - RHiME, Editor (Research and Humanities in Medical Education, 2020)
The Editorial Board of RHiME would like to thank the following reviewers for their outstanding contribution to the work of the journal. Without their dedication and the time they devoted to the evaluation of submissions made to RHiME, it would have been impossible to maintain the standards of the journal. Amir Maroof Khan Anirban Chatterjee Anshu Aqsa Shaikh Arjun Ravishankar Chinmay Shah Juhi Kalra Navjeevan Singh Pooja Priyamvada Raghavi Ravi Kasthuri Rajat Thawani Rimpi Gupta Roopa Ravindranath Sabita Shome Sanjoy Das SG Kabra Shalini Govil Sheela Jaywant Shruti Srivastava Sonal Pruthi Sukhmani Dhaliwal